Families' Knowledge, Attitudes, and Experiences of the Tissue Donation Process. (September 2013) - Luo, Jingjing; Rothnie, Alison; Sanderson, Elaine; Smith, Melissa; Cowie, Anne; Musiello, Toni
Context: Most existing research on the experiences of donor families has been focused on organ donation, with few studies pertaining specifically to the experiences of tissue donor families. Further investigation into tissue donation in Australia is needed in order to improve the process, support, and potential rate of tissue donation consent. Objective: To assess the experiences of families of recent tissue donors, to compare changes in the tissue donation process with previously published research, and to identify areas for improvement. Design: Cross-sectional survey by postal questionnaire. Setting and Participants: Families who consented to tissue donation through DonateLife Western Australia (the coordinating organization for deceased organ and tissue donation in Western Australia) between 2004 and 2009 were invited to participate. Main Outcome Measures: Donor families' experience, knowledge, and attitudes toward tissue donation and their satisfaction with the approach and quality/effectiveness of support services provided to donor families. Results: One hundred one (39%) of the 256 questionnaires were completed. Most respondents were satisfied with how they were approached, whether by phone or in person. Most participants who received ongoing support after donation (91%) found it beneficial. Nearly half (46%) of respondents supported the use of tissue for research; however, only 28% could recall the topic being discussed at the time of donation. Only 40% of respondents knew of the differences between organ and tissue donation before the donation process. Overall, respondents rated the experience of donating tissue as positive.